No independent or synergistic effects of carbohydrate-caffeine mouth rinse on repeated sprint performance during simulated soccer match play in male recreational soccer players. Issue 4 (2nd October 2022) - Gough, Lewis A.; Faghy, Mark; Clarke, Neil; Kelly, Adam L.; Cole, Matthew; Lun Foo, Wee
ABSTRACT: The study examined the synergistic and independent effects of carbohydrate-caffeine mouth rinse on repeated sprint performance during simulated soccer match play. Nine male soccer players (21 ± 3 years, 1.75 ± 0.05 m, 68.0 ± 9.0 kg) completed four trials with either 6 mg·kg −1 caffeine + 10% maltodextrin (CHO+CAFMR), 6 mg·kg −1 caffeine (CAFMR), 10% maltodextrin (CHOMR), water (PLA) in a block randomised, double-blinded, counterbalanced and crossover manner separated by minimum 96 h. All solutions were taste-matched and a carbohydrate-rich meal (2 g·kg −1 body mass) was provided 2 h before each trial. Each trial consisted of a 90-min soccer-specific aerobic field test (SAFT 90 ) and two bouts of repeated sprint ability tests (RSAT; 6 × 6 s sprints with 24 s recovery) completed at 0 min and 75 th min of SAFT 90 . A 25 ml solution of either CHO+CAFMR, CAFMR, CHOMR or PLA was rinsed immediately before the second RSAT (75 min). Mean power output, peak power output (PPO) or fatigue index (FI) was not impacted by any treatment during the 75 th min RAST (p > 0.05). These results suggest that carbohydrate and/or caffeine mouth rinses do not have an ergogenic effect during simulated soccer exercise after a high carbohydrate meal.